Modeling Bacillus cereus Growth and Cereulide Formation in Cereal-, Dairy-, Meat-, Vegetable-Based Food and Culture Medium - Ellouze, Mariem; Buss Da Silva, Nathália; Rouzeau-Szynalski, Katia; Coisne, Laura; Cantergiani, Frédérique; Baranyi, József (Frontiers in Microbiology, 2021)
Results showed that both growth and toxin-formation depend on the food matrix and on the environment but not in the same way. Thus, the matrix that supported the highest growth rates (culture medium) did not allow the shortest time to the appearance of quantifiable cereulide. While the cereal-based matrix generated the smallest growth rates (0.41-times smaller than culture medium did), it supported quantifiable cereulide at earlier times compared to the other tested matrices. In fact, three groups of matrices could be distinguished based on their ability to support cereulide formation (1) the cereal-based matrix, (highest) (2) the culture medium and the dairy-based matrix (medium) and (3) the meat- and vegetable-based matrices (lowest). This grouping is different when considering the matrices’ ability to support B. cereus growth. Our models can be used to perform, with improved accuracy, the microbiological food safety assessments of those products for which B. cereus is a main concern. The findings can be used to support HACCP studies or set appropriate products shelf life that are matrix-specific.